(untitled) (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study combining quantitative and qualitative approach, was carried out at the Cardiolgoy center of E Hospital in 2021. The study aimed to describe the current situation and analyze some factors affecting the performance of endoscopic device sterilization in cardiac surgery. The study conducted 150 times of observation of endoscopic device sterilization in cardiac surgery. The main findings showed that the rate of correct implementation of cleaning and disinfecting devices was 79.3% and sterilization was 87.3% at the department of infectious disease and control. Some influencing factors indicated that training for health staffs; supervision of the implementation; having appropriate reward and punishment mechanisms would contribute to improve of adherence to and properly implementation of endoscopic device sterilization in cardiac surgery.